The Relationship of Energy and Macro nutrient Intake on Fatigue Levels of Female Workers at The Bandarharjo Fish Smoking Center, Semarang City - Silitonga, Steward Febrianto; Suyatno, Suyatno; Asna, Alfi Fairuz; Kartasurya, Martha Irene (Journal of Public Health for Tropical and Coastal Region, 2022)
Introduction: Inadequate intake of energy and macronutrients causes a decrease in an individual's ability to carry out his work activities and makes him feel tired or tired more easily. The purpose of this study was to analyze the relationship between energy adequacy level (EAL) and protein adequacy level (PAL) as well as the percentage of carbohydrate intake and the percentage of fat intake with the fatigue level of female workers.Methods: This research is an analytic observational study with a cross-sectional design. The population in this study were 67 female workers at the Bandarharjo Fish Smoking Center, Semarang City. Research subjects were selected by purposive sampling of 40 subjects, based on inclusion criteria. EAL, PAL data were collected, as well as the percentage of carbohydrate and fat intake obtained through interviews using a 2x24 hour food recall form. Data analysis was performed by Pearson Product Moment correlation test on normally distributed data and Ranks Spearman correlation test on non-normally distributed data.Results: The results showed that the average EAL was 86,6 (±26,3)% energy requirement/day, PAL was 64,5 (±23,5)% protein requirement/day, the percentage of carbohydrate intake was 51,5 (±7,6)% energy intake/day, and the percentage of fat intake was 34,7 (±8,6)% energy intake/day, and the level of work fatigue with an average reaction time of 429,7 (±121,9) milliseconds. There was no relationship between EAL (r=0,127 and p=0,435), PAL (r=0,159 and p=0,327), percentage of carbohydrate intake (r=0,036 and p=0,825), and percentage of fat intake (r=-0,088 and p = 0,590) with the level of work fatigue.Conclusion: It can be concluded that there is no relationship between EAL, PAL, and the percentage of carbohydrate and fat intake with the level of work fatigue in female workers in the Bandarharjo Fish Smoking Center, Semarang City.